Deindustrialization: A view of the Brazilian economy (Research, Society and Development, 2020)
Despite being a worldwide studied topic, there are still few results in the literature on research carried out on deindustrialization in Brazil. The country experienced two crises in the period between 2001 and 2018, the first in the 2008-2009 biennium, when there was a recession in 2009, and the second in the 2015-2016 biennium, with recessions in 2015 and 2016. On average, in these almost two decades, the Brazilian Gross Domestic Product (GDP) grew 2.3% per year in real terms, while the expansion of GDP per capita was 1.2%. Then, in 2020, the COVID19 pandemic rocked the world economies, and Brazil's forecast of a drop in GDP participation is 5.8% according to estimates by the International Monetary Fund (IMF), where the initial forecast would be around 9.1 % considered to be the largest in 120 years. Brazilian industrial production has fallen since the 1940s. In the country, the term deindustrialization has been used since the 1970s to justify the relative loss of industrial employment; in 2020, this estimate is around 13.4% and may rise in 2021 as a forecast of around 14.1%. This exploratory study analyzed the phenomenon in manufacturing companies, based on data from the National Confederation of Industry, using the Human Development Index (HDI), Gross Domestic Product (GDP), and the Unemployment Index as the basis for each product studied. The results show a drop in the industrial production of the sectors studied, in Brazil, since 2005, mainly the metallurgy sector, pointing to a deindustrialization scenario.